2013
DOI: 10.2166/wh.2013.241
|View full text |Cite
|
Sign up to set email alerts
|

Microbial reduction in wastewater treatment using Fe3+ and Al3+ coagulants and PAA disinfectant

Abstract: Wastewater is an important source of pathogenic enteric microorganisms in surface water and a major contaminating agent of drinking water. Although primary and secondary wastewater treatments reduce the numbers of microorganisms in wastewater, significant numbers of microbes can still be present in the effluent. The aim of this study was to test the feasibility of tertiary treatment for municipal wastewater treatment plants (WWTPs) using PIX (FeCl 3 ) or PAX (AlCl 3 ) coagulants and peracetic acid (PAA) the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…in 50% of samples (2/4) collected after PAA disinfection underscores that the low doses of PAA used (0.99 mg/L and 1.06 mg/L) were likely not sufficient to remove Salmonella contamination in the final effluent. A total reduction of Salmonella (100%) was obtained by Pradhan et al [4] after wastewater disinfection by using a higher PAA concentration (3 mg/L). Another interesting study reported the presence of Salmonella in 28% of PAA disinfected effluents monitored in nine WWTPs along the coast of Venice province (Italy), but the authors did not report the values of the PAA doses used [21].…”
Section: Resultsmentioning
confidence: 96%
“…in 50% of samples (2/4) collected after PAA disinfection underscores that the low doses of PAA used (0.99 mg/L and 1.06 mg/L) were likely not sufficient to remove Salmonella contamination in the final effluent. A total reduction of Salmonella (100%) was obtained by Pradhan et al [4] after wastewater disinfection by using a higher PAA concentration (3 mg/L). Another interesting study reported the presence of Salmonella in 28% of PAA disinfected effluents monitored in nine WWTPs along the coast of Venice province (Italy), but the authors did not report the values of the PAA doses used [21].…”
Section: Resultsmentioning
confidence: 96%
“…Aluminium and iron salts in combination with PAA (3 or 5 mg/L with a contact time of 5 mins) have proven to be effective in tertiary treatment: especially non-sporing bacteria (such as campylobacteria) were eliminated effectively, whereas sporing bacteria (such as clostridia) and F-specific coliphage were more resistant [142]. Furthermore, no reduction in the number of noroviruses, rotaviruses, or adenoviruses as a result of PAA treatment of tertiary effluent was observed [142]. Recently PAA disinfection was studied in combination with the sequential batch biofilter granular reactor (SBBGR) and it was found that with a dose of 1 mg/L of PAA it was possible to reach E. coli < 10 CFU / 100 mL [143].…”
Section: Primary Secondary and Tertiary Wastewater Effluentsmentioning
confidence: 99%
“…PAA has been used as a cooling water biocide [32,162], as it has a good potential for the removal of Legionella pneumophila [142,[163][164][165]. The continuous doses used for Legionella removal varied considerably (3-1000 mg/L) and re-growth after treatment was reported [142,[163][164][165].…”
Section: Industrial Effluentsmentioning
confidence: 99%
See 2 more Smart Citations